Meningkatkan Pembelajaran Keterampilan Tata Rias Melalui Model Direct Instruction bagi Anak Tunarungu - Santi, Elia; Armaini, Armaini (Jurnal Penelitian Pendidikan Khusus, 2022)
This research motivated by probems that found at SLBN Sungai Penuh. Researchers found two deaf students class X/B has not been ale to do creambath to oilling hair properly. At learning process the teacher use lecture method, copying teachers wrote at whiteboard, so that students not antusistic and bored in learning process, and make just one way comunications. The teacher do demonstration less, so students not undestand about tools function and step in creambath. Based on that problems, to improve creambath skills learning, Direct Instruction model was given to improve creambath skills for deaf students class X/B at SLBN Sungai Penuh. The type of research that used was classroom action research consisting of two cycles with each cycle there are four meetings, each meeting consisting of planning, action, observation and reflection. In this study researchers collaborated with fashion teachers, researchers as implementers and fashion teachers as observers. The result show that initial skills score were AM  40,08 and RT  57,14.  After the first cycle, AM skills score 61,90 and RT 69,04. And then, After  the  second cycle AM skills score 90,47 dan RT 92, 85. The results showed that Direct Instruction model can to improve creambath skills for deaf students class X/B at SLBN Sungai Penuh.